Corrosion protection products as a source of bisphenol A and toxicity to the aquatic environment. (15th October 2017) - Vermeirssen, Etiënne L.M.; Dietschweiler, Conrad; Werner, Inge; Burkhardt, Michael
Abstract: Steel components are typically treated with anti-corrosion coatings like epoxy or polyurethane resins to protect the integrity and functioning of steel. Such resins may contain substances, such as bisphenol A (BPA), that have caused concern in a human and environmental toxicological context. We investigated the release of toxicity from four anti-corrosion coatings used in hydraulic and civil engineering. Resins were applied onto glass plates and leachate samples produced by horizontally shaking the plates in water for 7 days. Two experiments were conducted, one with a 1 day and one with a 7 day curing period. Using a suite of bioassays, we tested samples for: agonistic and antagonistic effects on various mammalian nuclear receptors; inhibition of photosynthesis and growth in algae; inhibition of bacterial bioluminescence; and inhibition of water flea reproduction. Concentrations of BPA, bisphenol F and various BPA transformation products were determined by chemical analysis (LC-MS/MS). Bioassay results were evaluated using a scheme developed by DIBt (Centre of Competence for Construction, Berlin, Germany). Three products induced responses in one or more of the measured endpoints and toxicity profiles varied markedly in intensity across products. One product released high amounts of BPA which was associated with effects on nuclear receptor transactivation, requiring a more than 700-fold dilution for effect induction to fall below 20%. The same product was also the most toxic to water flea reproduction, requiring ca. 70-fold dilution for effects to fall below 20%. Another product was highly toxic in terms of bacterial bioluminescence, particularly after a shorter curing time, requiring a ca. 1′300-fold dilution for effects to fall below 20%. The third product required a 22-fold dilution for inhibition of water flea reproduction to drop below 20%. Results show that anti-corrosion coatings based on epoxy resins can be a source of toxicity to the aquatic environment. The fact that some products are more toxic than others highlights opportunities for the development of low risk formulations and products with better environmental performance. Finally, the DIBt scheme provides a useful starting point to develop further ecotoxicity guidelines for testing and data evaluation of leachates from construction materials. Graphical abstract: Image 1 Highlights: Epoxy resin based anti-corrosion coatings can leach significant amounts of toxicity. One of four tested products released large amounts of bisphenol A (BPA). Ecotoxicity guidelines to test construction material leachates require development.